Increasing risk of postlung transplant hospitalizations for infection: An analysis of recent trends - Shi Nan Feng, BSPH; Armaan F. Akbar, BS; Alice L. Zhou, MS; Andrew Kalra, BS; Sean Agbor-Enoh, MD, PhD; Christian A. Merlo, MD, MPH; Errol L. Bush, MD (JHLT Open)
Background: Despite advancements in lung transplantation (LT), infection remains a major cause of morbidity and mortality following LT. We examined trends in hospitalizations for infection in the first year after LT. Methods: We identified adult LT recipients in the United States (March 1, 2018-March 9, 2023) using the Organ Procurement and Transplantation Network database. We categorized transplants into 3 eras to account for the Composite Allocation Score allocation policy change and coronavirus disease 2019: March 2018 to March 2020, March 2020 to March 2022, and March 2022 to March 9, 2023. One-year post-LT survival was compared using Kaplan-Meier survival analysis and Cox proportional hazards regression. Hospitalizations for infection were compared using multivariable logistic regression, adjusted for era and donor and recipient characteristics. Results: Of 12,388 LT recipients (median age = 62, male = 61.2%), hospitalization for infection in the first-year post transplant was 5.2% for patients transplanted from March 2018 to March 2020 (N = 5,031), 7.6% from March 2020 to March 2022 (N = 4,659), and 13.2% post-March 2022 (N = 3,640) (p < 0.001). Compared to March 2018 to March 2020, patients transplanted from March 2020 to March 2022 (adjusted aoods ratio [aOR] = 1.50, 95% confidence interval [CI] = 1.26-1.79) and post-March 2022 (aOR = 2.89, 95% CI = 2.29-3.65) were more likely to be hospitalized for an infection. After adjustment, we found no significant difference in risk of death following LT for recipients transplanted between March 2020 and March 2022 (aHR = 1.09, 95% CI = 0.96-1.23, p = 0.175) compared to March 2018 and March 2020. Post-March 2022 risk of death was elevated (aHR = 1.21, 95% CI = 1.04, 1.40, p = 0.014). Conclusions: Odds of hospitalization for infection in the first year after LT performed between March 2020 and March 2022 and post-March 2022 were 1.50 and 2.89 times as high, respectively, as LT performed between March 2018 and March 2020. IRB NUMBERS: IRB00352819